Cantilever-enhanced photoacoustic measurement of light-absorbing aerosols. Issue 1 (25th November 2021) - Karhu, Juho; Kuula, Joel; Virkkula, Aki; Timonen, Hilkka; Vainio, Markku; Hieta, Tuomas
Abstract: Photoacoustic detection is a sensitive method for measurement of light-absorbing particles directly in the aerosol phase. In this article, we demonstrate a new sensitive technique for photoacoustic aerosol absorption measurements using a cantilever microphone for the detection of the photoacoustic signal. Compared to conventional diaphragm microphones, a cantilever offers increased sensitivity by up to two orders of magnitude. The measurement setup uses a photoacoustic cell from Gasera PA201 gas measurement system, which we have adapted for aerosol measurements. Here we reached a noise level of 0.013 Mm −1 (one standard deviation) with a sampling time of 20 s, using a simple single-pass design without a need for a resonant acoustic cell. The sampling time includes 10 s signal averaging time and 10 s sample exchange, since the photoacoustic cell is designed for closed cell operation. We demonstrate the method in measurements of size-selected nigrosin particles and ambient black carbon. Due to the exceptional sensitivity, the technique shows great potential for applications where low detection limits are required, for example size-selected absorption measurements and black carbon detection in ultra clean environments.